Evaluation of WOMAC 20, 50, 70 response criteria in patients treated with hylan G-F 20 for knee osteoarthritis. Issue 6 (25th November 2004) - Bellamy, N; Bell, M J; Goldsmith, C H; Pericak, D; Walker, V; Raynauld, J P; Torrance, G W; Tugwell, P; Polisson, R
Abstract : Objective: A secondary analysis of a previously conducted one year randomised controlled trial to evaluate the capacity of responder criteria based on the WOMAC index to detect between treatment group differences. Methods: 255 patients with knee osteoarthritis were randomised to "appropriate care with hylan G-F 20" (AC+H) or "appropriate care without hylan G-F 20" (AC). In the original analysis, two definitions of patient response from baseline to month 12 were used: (1) at least a 20% reduction in WOMAC pain score (WOMAC 20P); (2) at least a 20% reduction in WOMAC pain score and at least a 20% reduction in either WOMAC function or stiffness score (WOMAC 20PFS). For this analysis, a responder was identified using 50% and 70% minimum clinically important response levels to investigate how increasing response affects the ability to detect treatment group differences. Results: The hylan G-F 20 group had numerically more responders using all patient responder criteria. Increasing the response level from 20% to 50% detected similar differences between treatment groups (25% to 29%). Increasing the response level to 70% reduced the differences between treatment groups (11% to 12%) to a point where the differences were not significant after Bonferroni adjustment. Conclusions: These results provide evidence for incorporating response levels (WOMAC 50) in clinical trials. While differences at the highest threshold (WOMAC 70) were not statistically detectable, an appropriately powered study may be capable of detecting differences even at this very high level of improvement.